Potential Infectious Complications in Pig Xenograft Donors and Recipients - Nicolas J. Mueller; Linda Scobie (Transplant International)
Preclinical and clinical xenotransplantation trials have shown that successful outcomes depend on a number of factors including the prevention of xenozoonoses. Preclinical trials involving pig kidneys and hearts transplanted into various non-human primates have revealed the potential impact of pig pathogens being present in the transplanted organ/tissue, mainly viruses. The concept of “designated pathogen-free donor animals” was developed to ensure elimination of pathogens during the breeding of donor animals to mitigate this occurrence. This is a challenging process as confirmation of presence and absence of some pathogen, in particular for latent viruses, requires a validated armamentarium of direct and indirect tests. The importance of using the correct diagnostic regimen was highlighted during the first pig-to-man cardiac transplantation with both porcine cytomegalovirus (PCMV), also known as porcine roseolovirus (PRV), and porcine circovirus (PCV) detected in the transplanted organ and in the patient. To further improve xenotransplantation and to achieve trials in Europe it is important that we use these data to inform process for diagnostics both in donor and recipients before and after xenotransplantation to ensure safety. As part of this sensitive and specific pathogen detection systems should be validated and readily available.